SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PRIORITAS STRATEGI DIGITALISASI UMKM DI KOTA LUBUKLINGGAU MENGGUNAKAN KOMBINASI METODE AHP DAN SAW - Desi Hartati; Wisnumurti Wisnumurti; Sri Tita Faulina; Endang Rahmayanti; Wenny Septafiana Aulia (Jurnal Teknologi Informasi Mura (JTI), 2026)
Micro, Small, and Medium Enterprises (MSMEs) are a vital pillar of the Indonesian economy, including in Lubuklinggau City. However, the digital transformation of MSMEs still faces various obstacles, such as low digital literacy among human resources, uneven information and communication technology (ICT) infrastructure, weak digital data security, and limited capital for digitalization investment. Various policy strategy alternatives have been proposed, yet local government requires an objective tool to determine which strategy should be prioritized given limited budget and time. This study aims to build a Decision Support System (DSS) model to determine the priority of MSME digitalization strategies in Lubuklinggau City using the Simple Additive Weighting (SAW) method. The study employs five evaluation criteria—impact on MSME performance, urgency, ease of implementation, implementation cost, and existing regulatory support—along with five policy strategy alternatives adapted from an MSME digitalization policy brief for Lubuklinggau City. The SAW calculation results show that the strategy of improving human resource capacity and digital literacy obtained the highest preference value (Vi = 0.970), followed by the integration of services through the Silampari Smart City platform (Vi = 0.753), capital assistance and digital access subsidies (Vi = 0.718), digital data security education (Vi = 0.690), and equitable distribution of ICT infrastructure (Vi = 0.665). These results indicate that the SAW method can serve as a systematic, transparent, and accountable decision-support tool for policymakers in formulating MSME digitalization program priorities.